Meckel’s Diverticulum in Children - Presentation & Management: 5 Year Experience At a Tertiary Care Hospital (Dhaka Shishu (Children) Hospital Journal, 2025)
Background: Meckel’s diverticulum (MD) is the most common congenital anomaly of the gastrointestinal (GI) tract. Early identification and appropriate surgical management are critical to prevent complications and improve outcomes. Objective: The aim of this study was to assess the presentation and management of Meckel’s Diverticulum in children. Methods: This retrospective study was conducted in the Division of Paediatric Surgery, Bangladesh Shishu Hospital & Institute, Dhaka from February 2019 to January 2023. Total 35 children admitted within this period due to Meckel’s Diverticulum were included in this study. Results: The participants’ mean age was 30.1 months (SD± 34.9 months) ranged between 0.5 to 156 months. There was male predominance (82.9%) among the study patients. Painless rectal bleeding was the most common symptom (34.28%), followed by inflammation/diverticulitis (25.71%), intussusception (lead point) (14.29%), incidental in 14.29%, and intestinal obstruction/acute abdomen (5.71%). No Surgical intervention was undertaken in 34.3% of cases, while laparotomy with wedge resection was done in 28.5% of cases. A laparotomy along with appendectomy was done in 17.1% of cases, laparotomy with resection and anastomosis was required 8.6% of the patients, and laparotomy with manual release of intussusception was done in 11.4% of the cases. The mean diverticulum distance from the ileocecal valve was 16.3 ± 2.1 cm. Postoperative complications included wound infections (14.29%) and adhesive obstruction (5.71%), with no mortality. Conclusion: This study highlights the effective management of Meckel’s Diverticulum in children, with favorable postoperative outcomes, low complication rates, and the importance of early diagnosis and appropriate surgical intervention in resource-limited settings.DS (Child) H J 2023; 39(2): 101-105